Ecologia e conservação de morcegos (Chiroptera) em cavernas no Sudeste do Tocantins, Brasil - Pereira, Jennifer de Sousa Barros (2018)
There are about 180 species of bats registered in Brazil, of which 58 occur in caves, and of these 13 are consider restrict to caves. Many species make use of caves as roost because they have high environmental stability and provide protection against predators and climatic adversities, allowing social interaction, reproduction and parental care. However, these environments, as well their associated fauna, became fragile due to changes made in Brazilian legislation in 2008, allowing irreversible negative impacts on caves that are subject to environmental licensing. In this way identify caves that represent important bats roost and understand what cave and landscape characteristics may influence the selection of shelter by them becomes necessary to define priority areas for conservation. Thus, the study aimed to identify priority caves for conservation taking into account richness, diversity and presence of threatened and/or resident species. And also verify the influence of abiotic variables of cave and the landscape on the richness, on bats assemblage composition and on each species. To accomplish this, analyzes of linear regression and model-based multivariate analysis were used, with cave and landscape variables. After two trips to the work field 585 bats were captured, belonging to seven families and 31 species. Four endangered species were recorded in 12 caves, eight caves showed high diversity and seven elevated richness. Thus, of the 19 caves studied, 15 priority caves were identified for conservation, and four new records were made for the state of Tocantins. Richness and composition of the bat assemblage in the region of Aurora do Tocantins, Combinado and Lavandeira are determined by internal factors of the caves, being this relationship more evident during the dry season . The richness is positively related to the size of the caves, their stability in relation to the external environment and the different temperatures and humidity levels found in their interior. However, higher mean temperatures and greater heterogeneity of microhabitats are negatively related to the number of species. Although the heterogeneity of microhabitats was not positively correlated with richness, the quantity of each one of them had a significant contribution in the variation of the composition between the caves, acting together with their size. The variation in composition is a reflection of the characteristic preferences of each species, and it is possible to observe a general pattern of negative relations with higher temperatures, and positive with the other characteristics of the cave. The landscape, however, only showed significant influence for the presence of some species, presenting positive correlations with preserved areas and negative with degraded areas. Thus, it highlights the great potential of the area for the conservation of endangered species and it is suggested the integral protection of at least the classified caves with the maximum relevance. In addition, the present study provides relevant information on the ecological preference of bats for the roost selection that can be useful in decision making in environmental licensing processes.